Monetary Policy and Corporate Risk-Taking: Evidence From an Emerging Market - Tran, Quoc Trung; Truong, Thi Thuy Trang (The Indonesian Capital Market Review, 2021)
This study examines how monetary loosening influences risk-taking of companies listed in Vietnamese stock exchanges in the period from 2009 to 2019. Our research sample consists of 4,358 observations from 566 listed firms. Using the Pooled OLS regression model, we find that expansionary policy increases corporate risk-taking. Our research findings also demonstrate that firms with high leverage engage more in risk-taking activities, while firm size, state ownership and foreign ownership negatively affects corporate risk-taking. The research results imply that corporate managers, shareholders and policymakers in emerging markets should consider the nexus between monetary policy and corporate risk-taking levels during their decision-making process.